Model Pengukuran Performansi Rantai Pasok Industri Makanan Kaleng Dengan Pendekatan SCOR - Yulinda Uswatun Kasanah; Miftahol Arifin (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
The canned food industry is experiencing growth in this modern era. Canned food has become a popular choice due to its convenience in storage and preparation. Canned food manufacturers continue to develop new products and improve the quality of existing products to meet the increasingly diverse consumer demand. Challenges in improving company performance require companies in the canned food industry to constantly enhance the performance of their supply chains to remain competitive in the global market. This research aims to measure the performance of the canned food industry supply chain by implementing SCOR and integrating it with AHP. Based on the performance measurement results, PT XZY, a canned food company, has a SCOR score of 76.58, indicating that the company's performance is considered good. The lowest KPIs are Delivery performance and Return performance.